(untitled) (Sains Humanika, 2014)
The main aim of this study is to test the motivation variable as an appropriate mediator variable between teaching process and guidance of teacher and self-directed learning students in secondary schools in Sabah. Besides that, this study was carried out to establish student’s perception on concerned variables. This quantitative study used the survey method involving 407 students from urban area (205 students) and rural area (202 students). This study referred to Self-Regulated Learning Model (Borkowski & Dukewich, 1996) as the research framework basic model. Data collected were analysed using SPSS version 15 and AMOS version 4. Data analysis was carried out descriptively and inferential analysis (t-test, one-way ANOVA, Pearson Correlation, and Multiple Regression) was also used. The main result of the study indicated motivation was an appropriate mediator variable between teaching and guiding variables and self-regulated learning of student variable. The analysis path of structural equation modelling showed data used in this study had logical appropriateness for suggested regression model. Hence, it proved that the two concerned independent variables had direct and indirect relationship with dependent variable of this study which was self-regulated learning. Pearson correlation analysis showed there was a positive and significant relationship between variables of this study. This study also illustrated there was no significant difference in the mean score between urban students and rural students for motivation variable. It is hoped that this study can provide useful input for the improvement of national education system.